Why am I grinding and clenching? Exploration of personality traits, coping strategies, oral parafunctional behaviors, and severe sleep bruxism in a polysomnographic study - Wieczorek, Tomasz; Jodkowska, Anna; Orzeszek, Sylwia; Wieckiewicz, Mieszko; Michalek-Zrabkowska, Monika; Mazur, Grzegorz; Rymaszewska, Joanna; Smardz, Joanna; Wojakowska, Anna; Martynowicz, Helena (Frontiers in Psychiatry, 2024)
Causal relationships between psychopathological symptoms, personality traits, coping mechanisms, and sleep bruxism (SB) were studied in the past, giving inconsistent results mostly based on self-assessment evaluations. This polysomnography-based cross-sectional study aimed to explore the relationships between severe SB, personality traits (according to the Big Five model), and coping strategies with objective polysomnographic verification.The study included 66 participants divided into severe SB (SSB) (n=32) and no or mild SB (n=34) groups based on video-polysomnography performed in the sleep laboratory. Questionnaire assessment included the use of the Beck Depression Inventory, Beck Anxiety Inventory, Mini-COPE, International Personality Item Pool Big Five Markers 20-Item version, and Oral Behavior Checklist.Participants with SSB presented with fewer self-reported anxiety (p=0.008) and depressive (p=0.01) symptoms than the non-or mild-SB groups. The SSB group scored significantly higher in Big Five personal traits such as extraversion (p=0.007), emotional stability (p=0.013), and intellect (p=0.004), while regarding coping strategies, the SSB group was less likely to use negative strategies: self-distraction (p=0.036), denial (p=0.006), venting (p=0.03), behavioral disengagement (p=0.046), and self-blame (p=0.003), and turning to religion (p=0.041). The intensity of oral parafunctional behaviors was comparable in both groups (p=0.054). Emotional stability was a moderate protective factor (p=0.004), and the self-blame strategy was a strong risk factor (p<0.001) for increased oral parafunctional behavior intensity. Phasic activity negatively correlated with anxiety symptom severity (p=0.005), whereas tonic (p=0.122) and mixed (p=0.053) phenotypes did not. SB intensity was a protective factor against anxiety symptoms (p=0.016).In terms of psychopathology, severe sleep bruxers tend to present less severe anxiety and depressive symptoms, while some of their personality traits (extraversion, emotional stability, and intellect) were more strongly pronounced. SSB is possibly related to the lesser use of the "maladaptive" coping strategies and there were no specific coping strategies preferred by SSB participants, compared to the other group. These observations require further studies, as it should be determined whether SB (especially phasic activity) might be a form of a somatization/functional disorder. Further research should focus on the psychogenic background of oral parafunctional behaviors, which occur more often in less emotionally stable personalities and in people using selfblame coping strategies.